Corruption and the Lava Jato scandal in Latin America
1 online resource (xviii, 249 pages)
Keywords: "Corruption and the Lava Jato Scandal in Latin America brings together key international and interdisciplinary perspectives to shine new light on Lava Jato, or Operation Car Wash, Latin America's largest corruption scandal to date. Since 2014, this scandal has unfolded in surprising ways to expose collusion between construction companies and state officials in Brazil and 11 other countries. The corruption uncovered amounts to hundreds of millions of dollars in bribes and billions of dollars in stolen state funds. The volume features evidence that the main construction company at the center of the scandal was apparently deliberate about seeking business in corrupt markets. It also evaluates the ambiguous role played by the media, whose members often relied uncritically on classified information released by the authorities. The volume further contributes to our understanding with studies on a number of other relevant topics, including: the overlap between corruption and the planning of the Rio Olympics; Mexico and Peru's contrasting responses to Lava Jato; the policy reforms needed to avoid a similar scandal in the future; and the roadmap for how Lava Jato should end. Across fifteen chapters by leading and emerging scholars and practitioners, this book engages with these issues from a balanced and unbiased perspective, including interviews with key stakeholders on both sides of the case. As one of the first book-length studies to deal with Lava Jato in the English language, this ground-breaking volume is a compelling reading for advanced students and researchers in areas including Corruption Studies, Public Ethics, Political Science and Latin American Studies, as well as for practitioners working to make governments more accountable"--